Analisis Konteks Wacana Dalam Novel Selembar Itu Berarti Karya Suryaman Amipriono - Ismi, Adela; Rahayu, Sri (J-LELC: Journal of Language Education, Linguistics, and Culture, 2021)
Every story is built by context. Without context, there is no story because the context of the discourse builds it. Every reading, one of which is novel reading, is built by context. Context is used to understand a story, because context determines the meaning of speech so that it can interpret the situation or scope of language in discourse. The problem in this research is how the discourse context in the novel Selembar Itu Means is Suryaman Amipriono's work related to the setting and scene, participants, message, key, instrument, norms. , and what kind (genre)? The purpose of this research is to describe, analyze, and interpret the discourse context in Suryamana Amipriono's novel Selembar Itu Means. The theory used in this research is a theory in which there is a discourse context as stated by Hymes in Darma (2013) and other supporting theories. The source of data in this study is the source of written data, namely the novel Selembar Itu Berarti by Suryaman Amipriono. The data in this study are elements of discourse context. The method used in this research is descriptive method, qualitative approach, this type of research is a library (Library Research). Data collection techniques using hermeneutical techniques. The results of this study found eight elements of context in the novel Selembar Itu Means by Suryaman Amipriono, namely (1) forty-seven settings and scenes, (2) twenty-three participants, (3) the results (ends) were found as many as fifteen data, (4) the message (message) was found as many as twenty-three data, (5) how (key) was found as many as nineteen data, (6) the means (instrument) was found as much as one data, 7) twelve data found norms (norms), (8) one data type (genre) was found. It can be concluded that in Suryaman Amipriono's novel Selembar Itu Mean, there are eight elements of discourse context. In a novel, it is very rare to find no eight elements of discourse context. Because the context of discourse is the most important element in building a story.